EFFECT OF VARIATION OF MAGNETIC INDUCTION SOLENOID VALUES ON TENSILE AND IMPACT STRENGTH FOR WELDING BETWEEN LOW CARBON STEEL AND MEDIUM CARBON STEEL - Pribadi , Aries Fajar; Alamsyah, Fikrul Akbar; Hidayat , Wahyu; Prayudi , Makrusy Eko; Masykur , M Alfin; Solihin, Ihin; Raharjo, Rudianto (International Journal of Mechanical Engineering Technologies and Applications, 2024)
The use of solenoid magnets in welding processes has attracted attention due to their potential to influence the properties of welded joints. This research investigates the effect of the size of the magnetic induction solenoid on the tensile strength and impact toughness of welds between mild steel and medium carbon steel. Welding experiments were carried out using various sizes of solenoid magnets (0; 1.71mT; 2.11mT; 2.31mT; 2.60mT), and the welding results were tested for tensile strength and impact toughness. The findings show that the size of the magnetic induction solenoid has a significant effect on the mechanical properties of the weld. The larger induction size in this study increased the tensile strength of the welded joint, namely 431.576 N/mm2 without induction and 533.33 N/mm2 with induction. Meanwhile, the impact toughness of welded joints also increases, namely 95.92N.m without treatment and 217.35N.m with induction.